Evaluation of carbon dioxide emissions in Malaysia's highlands using airborne remote sensing / Dr. Norhusna Mohamad Nor and Nur Syifa Salim - Mohamad Nor, Norhusna; Salim, Nur Syifa (2020)
Environmental issue is one of the serious issues affecting the ecosystem. Release of CO2 emissions is really important that need to be considered. Most of spatial region at highlands in Malaysia were affected due to the excessive release of CO2 emissions and many changes occur such as air temperature and atmospheric moisture changes. However, some previous study shows that the CO2 emission forecasting is hardly being considered on multiple factors. Therefore, the Grey Relational Analysis approach was proposed in this study to investigate the correlation between multiple factors and CO2 emission signified the objective of this study which to analyse the CO2 emission data in Malaysia’s highlands using correlation coefficient analysis (GRA) method. The satellite database remote sensing that suitably used for the collection of the data is Giovanni which correlate to the objective in collecting CO2 emission data. The comparison between the multiple factors shows that the proposed method has higher accuracy compared on forecasting method presenting that correlation between atmospheric moisture and CO2 emissions has the significant outcomes in proving the factors that been affected by the CO2 emissions. From result analysed by GRA method, presenting the most affected factors due to the CO2 emissions is atmospheric moisture within Cameron Highland as it states the higher grey relational degree compared to the other associated factor within other highlands in 2009 and 2011 which were 2.812451 and 2.394842 respectively. While in 2010, the atmospheric moisture within Kundasang is the most greatly been affected by the CO2 emissions based on higher grey relational degree between other highlands which about 1.705437. Thus, the studying in satellite database remote sensing in analysing CO2 emissions in Malaysia’s highlands can be proved in this study.